Description Of The Quality Of Hospital Liquid Waste Processing In Controlling Chemical Parameters : Literature Review - Zairinayati, Zairinayati; Rashid, Norhashima Abd; Tan, Chun Hoe (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Introduction: Apart from being a health service facility, hospitals are also a medium for disease transmission for patients, employees, visitors and the community around the hospital. Many activities in hospitals have the potential to increase environmental pollution because every activity produces waste. The aim of this research is to obtain an overview of liquid waste management in preventing environmental pollution in hospitals. Material and Methods: This research uses the literature study method (literature review). The population is 4 journals and journals published are limited to the last 5 (five) years. Analysis used with PICO. Results: The results of this research are that liquid waste produced by hospitals includes waste water originating from the canteen and nutrition kitchen, waste water originating from inpatient rooms, waste water originating from central operating/surgery rooms, waste water originating from isolation rooms, waste water originating from outpatient rooms/polyclinics, waste water originating from pharmacy rooms, waste water originating from obstetrics rooms, and waste water originating from laboratories. All waste water is channeled to the IPAL, except for waste water that comes from nutritional kitchens, laundry and laboratories, because it must betreatment especially before heading to IPA. Conclusion: concluded that liquid waste processing in hospitals still does not meet hospital liquid waste quality standards, so supervision and monitoring by the government needs to be improved.